Early and annual projected savings from anti-CGRP monoclonal antibodies in migraine prevention: a cost-benefit analysis in the working-age population - Carlos Lazaro-Hernandez; Edoardo Caronna; Joana Rosell-Mirmi; Victor J Gallardo; Alicia Alpuente; Marta Torres-Ferrus; Patricia Pozo-Rosich (The Journal of Headache and Pain, 2024)
Abstract Background Migraine is one of the main causes of disability worldwide. Anti-CGRP monoclonal antibodies (MAbs) have proven to be safe and efficacious as preventive migraine treatments. However, their use is restricted in many countries due to their apparently high cost. Cost-benefit studies are needed. Objective To study the cost-benefit of anti-CGRP MAbs in working-age patients with migraine. Methods This is a prospective cohort study of consecutive migraine patients treated with anti-CGRP MAbs (erenumab, fremanezumab and galcanezumab) following National reimbursement policy in a specialized headache clinic. Migraine characteristics and the work impact scale (WPAI) were compared between baseline (M0) and after 3 (M3) and 6 months (M6) of treatment. Using WPAI and the municipal average hourly wage, we calculated indirect costs (absenteeism and presenteeism) at each time point. Direct costs (emergency visits, acute medication use) were also analysed. A cost-benefit study was performed considering the different costs and savings of treating with MAbs. Based on these data an annual projection was conducted. Results From 256 treated working-age patients, 148 were employed (89.2% women; mean age 48.0 ± 8.5 years), of which 41.2% (61/148) were responders (> 50% reduction in monthly headache days (MHD)). Statistically significant reductions between M0 and M3/M6 were found in absenteeism (p < 0.001) and presenteeism (p < 0.001). Average savings in indirect costs per patient at M3 were absenteeism 105.4 euros/month and presenteeism 394.3 euros/month, similar for M6. Considering the monthly cost of anti-CGRP MAbs, the cost-benefit analysis showed savings of 159.8 euros per patient at M3, with an annual projected savings of 639.2 euros/patient. Both responders and partial responders (30–50% reduction in MHD) presented a positive cost-benefit balance. The overall savings of the cohort at M3/M6 compensated the negative cost-benefit balance for non-responders (< 30% reduction in MHD). Conclusion Anti-CGRP MAbs have a positive impact in the workforce significantly reducing absenteeism and presenteeism. In Spain, this benefit overcomes the expenses derived from their use already at 3 months and is potentially sustainable at longer term; also in patients who are only partial responders, prompting reconsideration of current reimbursement criteria and motivating the extension of similar cost-benefit studies in other countries.